2018
DOI: 10.1107/s2053229618015620
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I) iodide ribbons coordinated with thiourea derivatives

Abstract: Two products of the reactions of CuI with 1-benzoyl-3-(4-bromophenyl)thiourea and with 1-benzoyl-3-(2-iodophenyl)thiourea have been obtained and characterized, namely poly[[[1-benzoyl-3-(4-bromophenyl)thiourea-κS]-μ3-iodido-copper(I)] acetone hemisolvate], {[CuI(C14H11BrN2OS)]·0.5C3H6O} n , and poly[μ4-iodido-μ3-iodido-[N-(benzo[d]thiazol-2-yl)benzamide-κN]dicopper(I)], [Cu2I2(C14H10N2OS)] n . Their structures, determined by single-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The solid state structures of the dimeric complexes 2a , 2b , 2c , and 2e (Figure ) share some of the main features found in the structures of the analogous dimeric complexes derived from phenyl phosphinites . Thus, the Ni centers in all dimers adopt a geometry that is very close to square planar, with τ 4 values ranging from 0.05–0.07 for dimers sitting on an inversion center ( 2c and 2e ) and 0.08–0.13 for those not generated by a symmetry operation ( 2a and 2b ). However, the Ni−μ-Br–Ni angle in 2a was found significantly smaller than the others (85–87° vs <92°), which translates into a noncoplanarity of the two halves of the dimer (Table ).…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…The solid state structures of the dimeric complexes 2a , 2b , 2c , and 2e (Figure ) share some of the main features found in the structures of the analogous dimeric complexes derived from phenyl phosphinites . Thus, the Ni centers in all dimers adopt a geometry that is very close to square planar, with τ 4 values ranging from 0.05–0.07 for dimers sitting on an inversion center ( 2c and 2e ) and 0.08–0.13 for those not generated by a symmetry operation ( 2a and 2b ). However, the Ni−μ-Br–Ni angle in 2a was found significantly smaller than the others (85–87° vs <92°), which translates into a noncoplanarity of the two halves of the dimer (Table ).…”
Section: Resultsmentioning
confidence: 57%
“…Consistent with this, the molecular diagram of 2f-L (Scheme ) revealed a very distorted structure in which the steric repulsion between C8–H and the phosphinite has caused a significant twist around the Ni–C1 axis. Indeed, the tetrahedral distortion parameter τ 4 around the Ni center was found to be 0.30–0.35, caused primarily by the out-of-plane displacement of the non metalated naphthyl phosphinite ligand. As a result, the dihedral angle of ca.…”
Section: Resultsmentioning
confidence: 99%
“…that they form rack-type layers parallel to the (001) plane. In our previous work (Rosiak et al, 2018b), we showed that this compound in reaction with CuI undergoes dehalogenation and cyclization to form N-(benzo[d]thiazol-2-yl)benzamide. It then serves as an N-donor ligand stabilizing quadruple CuI chains.…”
Section: Ringmentioning
confidence: 99%
“…The simultaneous presence of sulfur and oxygen electronpair donors (and potential nitrogen donors upon deprotonation; Rosiak et al, 2018b) causes the versatility in the behaviour of acylthioureas as building blocks of crystal frameworks. Because of the partial double-bond character of the C-N bonds in (thio)ureas, S, U, M and Z conformational isomers can be distinguished, depending on the mutual position of the carbonyl and thiocarbonyl groups (Woldu & Dillen, 2008).…”
Section: Introductionmentioning
confidence: 99%